Reliability and validity of Turkish version of COPD Assessment Test - Yorgancio?lu, Arzu; Polatli, Mehmet; Aydemir, Ömer; Yilmaz Demirci, Nilgün; Kirkil, Gamze; Nayci Atiş, Sibel; Günakan, Gonca (Ankara University, 2012)
Introduction: This study is aimed to evaluate the reliability and validity of the Turkish version of chronic obstructive pulmonary disease (COPD) Assessment Test (CAT) in seven centers. Materials and Methods: 321 patients between 4-75 years of age, diagnosed and staged by Global Initiative for Obstructive Lung Disease (GOLD) 2011 criteria were included. The Breathlessness, Cough, Sputum scale (BCSS), mMRC (Modified Medical Research Council) dyspnea index, St. George Respiratory Questionnaire (SGRQ), CAT and Short Form-36 (SF-36) were used concurrently. In the statistical analyses, internal consistency, item-total score correlation, explorative factor analysis, correlation with other scales were calculated. Results: The mean age was 62.4 ± 8.9 years and 89.7% of the patients were male (n= 288). Mean FEV 1% was 51.9 ± 19.2 and most of the patients were in Stage 3. CAT total score was 17.8 ± 9.5. In the internal consistency, Cronbach alpha coefficient was found as 0.9116 and item-total score correlation coefficients were between 0.62-0.79 and all were statistically significant (p< 0.0001). The correlation of the test-retest score calculated after two weeks with the initial score was 0.96 (p< 0.0001). In the structural validity, factor analysis with principle component analysis and varimax rotation was performed. One factor solution was achieved with eigenvalue of 4.956 and it represented 61.9% of the total variance. All the items were contained in the factor and the factor loads were between 0.71-0.85. The correlation coefficients of CAT with other indexes were moderate to good. The discrimination of CAT among disease stages has been shown to be significant (p< 0.0001) and a significant correlation was found with pulmonary function tests (p< 0.0001). Conclusion: It is demonstrated The Turkish version of COPD Assessment Tool is reliable and valid.
KOAH de?erlendirme testinin Türkçe geçerlilik ve güvenilirli?i
Keywords: CAT; COPD; Reliability; Validity